Avaliação da eficiência de coagulantes naturais a base de tanino para o tratamento de água preta do Município de Itacoatiara-AM. - Leite, Layane Kaliny de Souza (Brasil, 2022)
Water is a fundamental resource for the survival of living beings, but due to pollution caused by the inappropriate disposal of garbage, sewage and even industrial waste, it becomes unsuitable for consumption. In view of this problem, it is necessary to carry out treatments to remove pollutants, which involve processes with several steps, including coagulation. This work aims to evaluate the performance of natural coagulants tannins base for the treatment of black water. 20 to 40L of water were collected from Lago de Serpa and Rio Urubu in the municipality of Itacoatiara and evaluated the physical-chemical parameters pH, electrical conductivity, temperature by electrometry, color by spectrophotometry, turbidity by turbidimetry and suspended solids by gravimetry. To determine the amount of coagulant, the jar test was applied, using the coagulants Tanfloc SG®️, Tanfloc MTH®️ and Tanfloc MT®️. For each coagulant, a stock solution at a concentration of 1.0%(m/v) was prepared. Five 1.0L jars were used, in which raw water and the following volume aliquots of the mother solution were added: 1.0; 2.0; 3.0; 4.0 ml. In raw water values were found from 184.85 to 228.34 mg Pt/L for apparent color and 65.20 to 122.51 mg Pt /L for real color. Regarding the amount of suspended solids, there was an increase from 1.0 to 2.50 mg/L. The pH ranged from 6.22 to 6.61 for raw water and varied from 6.22 to 8.38 for treated water. The electrical conductivity ranged from 24.2 to 29.5 µS/cm. Turbidity increased from 7.02 to 15.20 NTU in raw water during collections. The turbidity for treated water had variations between. For treated water, color removal was found to be 82.52% for SG, 98.63% for MT and 99.86% for MTH and turbidity removal of 100% for SG, 98.88% for the MT and 100% for the MTH. The pH value of the water treated in these removals ranged from 6.31 to 8.52 for Lago de Serpa and 6.52 to 7.16 for the Urubu River. Thus, it was concluded that the coagulants used in the treatment of black water are efficient in removing color and turbidity; in addition to maintaining a practically constant pH and within the range required by current legislation on drinking water.